ONParkinson – Innovative mHealth to support the triad: patient, carer and health professional - Madeira, Rui Neves; Pereira, Carla Mendes; Clipei, Sergiu; Macedo, Patrícia (My University, 2016)
The ONParkinson mHealth platform aims to empower an integrated assistance to support end-users of the triad “people with Parkinson’s Disease, their carers and health professionals”, promoting the self-management in Parkinson’s disease. Therefore, ONParkinson is expected to optimize the communication between the triad users, helping them find relevant knowledge to support their clinical issues, as well as allowing the monitoring of patients` daily routine and the recommendation for daily exercises. This mHealth solution was created and materialized after an initial study of the end-users’ needs. This paper presents the usability study of the first version of the ONParkinson prototype. According to the usability tests’ findings, ONParkinson was perceived by the triad users as easy to use, with functionalities well integrated, useful and attractive. Some recommendations were suggested to enhance its usability, users’ satisfaction and continuance intentions.
Trabalho apresentado no 6th EAI International Symposium on Pervasive Computing Paradigms for Mental Health, 28-30 novembro 2016, Barcelona, Espanha
Keywords: Parkinson’s disease; mHealth; mobile computing; usability; self-management